Design and Performance Research of Detection Platform based on Spherical Parallel Mechanism - Zhu Xiaorong Zhou Yudong Hu Yang Song Yueyue Deng Jiaming Shen Huiping (Jixie chuandong)
In order to improve the accuracy of automatic visual inspection of photoelectric products，a kind of prototype of 4SPS/S spherical parallel mechanism (PM) adjustment platform with redundant driving branches is developed. The redundant 4SPS/S PM is of three-rotational degrees of freedom（DOF）around the center of the platform and used for obtaining the image information of the inspected parts from arbitrary angle. Firstly，the kinematics model of the PM is established, and the forward and inverse kinematics equations and Jacobian matrix are derived. Moreover，the singularity is discussed based on Jacobian matrix in terms of rank deficiency, and it is also proved that the redundant drive branch chain can eliminate the singularity in the mechanism. Based on non-redundant decomposition of Jacobian matrix，an evaluation index of force transmissibility suitable for redundantly PM is proposed. Secondly，the influence of the spherical joints layout on kinematical performance of the PM is analyzed，and a set of layout of the spherical joints with large attitude space and good dexterity is obtained. Further，the prototype of spherical parallel detection platform is designed and manufactured. Finally，the distribution of posture space, dexterity and force transfer performance of the prototype in posture space is analyzed and drawn. The results show that the prototype has large rotation space, no internal singularity, high dexterity and force transfer performance, and uniform distribution，which can meet the detection process requirements of photoelectric product.